Design and Implementation of a T-Type Based Topology for Grid-Connected Current-Source Inverters in PV Applications - Haupt, Douglas (2022)
This paper presents a novel non-isolated 5-level inverter for interfacing renewable sources to the power grid. It consists of a modified T-type converter with an HERIC-based AC decoupling strategy. The 5-level output voltage is filtered by a passively damped LCL filter, resulting in a high power density structure. Experimental results on a scaled-down 250 W prototype are presented to validate the operating principle of the proposed topology and show a high efficiency over the entire output power range. Besides, the injected current complies with the IEEE 1547-2018 specifications regarding harmonic content until the 10th harmonic, using a classical PI controller with an additional feedforward term.